2017
DOI: 10.1097/bpb.0000000000000320
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin-D measurement in patients with adolescent idiopathic scoliosis

Abstract: Our retrospective study compared vitamin-D levels in 229 patients with adolescent idiopathic scoliosis (AIS) and 389 age-matched controls, and evaluated the correlation between vitamin-D levels and sex, Cobb's angle, and serum levels of calcium (Ca), phosphorus, and alkaline phosphatase in the AIS group. Vitamin-D levels were lower in the AIS group, with no sex-specific effects, indicative of a possible vitamin-D resistance in AIS. Vitamin-D levels correlated positively with Ca levels and negatively with Cobb'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
67
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(86 citation statements)
references
References 27 publications
14
67
2
3
Order By: Relevance
“…Some studies noticed a possible association between vitamin D levels and scoliosis [2,52]. Balioglu et al found lower vitamin D levels and a positive correlation between vitamin D levels and calcium levels [53]. In our research all patients had a vitamin D deficiency, although the calcium level was normal.…”
Section: Discussionsupporting
confidence: 51%
“…Some studies noticed a possible association between vitamin D levels and scoliosis [2,52]. Balioglu et al found lower vitamin D levels and a positive correlation between vitamin D levels and calcium levels [53]. In our research all patients had a vitamin D deficiency, although the calcium level was normal.…”
Section: Discussionsupporting
confidence: 51%
“…No relationship was observed between vitamin D levels and Cobb angle in this study, which contradicts the single study found in the literature that correlated the two variables and showed an inverse relationship 12 . Furthermore, no relationship was found between 25-OHD levels and quality of life assessment.…”
Section: Discussioncontrasting
confidence: 99%
“…Recent studies indicate an interaction between 25-OHD deficiency and development of AIS, 11 , 12 which was corroborated in our study: almost all of the patients (97%) had lower 25-OHD levels than expected. Considering the small number of studies suggesting a correlation between 25-OHD and AIS, further studies are needed to support this hypothesis and to the reasons behind this variation.…”
Section: Discussionsupporting
confidence: 91%
“…As higher levels of vitamin D correlate with greater bone mineral density, several researchers have questioned the role of vitamin D in AIS. Furthermore, recent studies have shown a relationship between gene polymorphisms of vitamin D receptors (VDRs) and low bone mineral density [37]. Suh et al reported that the VDR BsmI polymorphism is associated with low bone mineral density at the lumbar spine (LSBMD) in girls with AIS [38].…”
Section: Vitamin Dmentioning
confidence: 99%